(untitled) (Global Journal of Science Frontier Research, 2014)
A survey of natural vegetation of Tehsil Takht-e-Nasrati, District Karak was undertaken in spring 2010-2011. Total 66 species were recorded during spring. Hierarchical Cluster Analysis (HCA), and Detrended Correspondence Analysis (DCA) were used for the plant community analysis. Plant species of each community type are presented together with the information on dominance and sub-dominance species. Four plant co-mmunities association i.e. Prosopis-Fagonia-Saccharum association, Zizyphus-Saccharum-Acacia association, Fagonia-Zizyphus-Eragrostis association and Aerua-Acacia-Cymbopogon association were recognized. Classification and ordination techniques provided very similar results based on the floristic composition and communities similarity. The results produced the source for the mapping division of plant life communities.